INTERPASSIVITY AS A SUBJECTIVE EFFECT OF MODERN MEDIA-CULTURE: TO THE STATEMENT OF PROBLEM - Olena V. Khodus (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose. In this article, research interest is fixed directly on the circumstances theming access personal / private as interpassivity practice of subjective life and creativity, which are mediated by modern media discourse. Methodology. Methodological base of research of contemporary experience of subjectivity is heuristic "ontological turn" in social theory, which allows to consider the subjectivity not as a reality (given), but as a procedural phenomenon, performativity, which exist in conditions of unstable ontologies, world without guarantees, indirect, thus, mass-media representations. Particular emphasis is placed on the deconstruction of traditional oppositions "objective/subjective", "public/private", "active/passive". As a result, a special interest in issues of privacy as "the place" in which the modern subject unstable ontology prefers to realize its self. Scientific novelty. It is proved that in the modern media culture, the subject is not so much a passive spectator, observer, collector information and events to represent relevant interested agents. He also actively reproduces itself in a form of "perceived privacy", which allows special mode of the experiences of private emotions "alone with everybody." Perceived privacy, although the individual reserves the right to individual control over personal space and personal statement (for example, through personal and individual electronic access to digital representations of reality), however, suggests certain techniques of "publication" themselves. It is the question of the interpassivity nature of such practices subjective life and creativity. Conclusions. Proposed research optics suggests that the person remains - the world-making being, who actively constructs their personal reality, however, when this reality is mediated by media representations, life world turns into a ready code, respectively, the active construction becomes superfluous. On the contrary, interpassivity as «activity through another» becomes the defining principle of relationship with the world.